Clinical Spectrum and Laboratory Study of Von Willebrand Disease -Experience from Tertiary Care Hospital in Pakistan - Hussain, Mohsin; Mahmood, Asad; Mahmood, Rafia; Khurshid, Ayesha; Khan, Nabeela; Sarwar, Nozaif (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the clinical features and laboratory parameters of patients of von Willebrand disease (vWD) in our population. Study Design: Cross-sectional study. Place and Duration of Study: Department of Hematology, Armed Forces Institute of Pathology (AFIP), Rawalpindi Pakistan, from Jan to Jul 2019. Methodology: All patients newly diagnosed von Willebrand disease patients were assessed clinically. Complete blood counts, bleeding time, coagulation profile, von Willebrand antigen levels and FVIII levels were determined. Results: A total of 66diagnosed patients of von Willebrand disease were included in the study. Out of these 15 (22.7%) were male while 51 (77.2%) were females. The most common clinical symptom was pallor, seen in 49 (74.2%) patients, followed by epistaxis in 36 (54.5%) and gum bleeding in 28 (42.4%) patients. Consanguineous marriages were found in 40 cases (60.6%) and family history was positive in 23 (34.8%). Patients mean vWF Ag level was4.29 ± 7.7 IU/dL while mean FVIII levels was 5.18 ± 7.8 1 U/mL. Conclusion: Von Willebr and disease is among the most common inherited bleeding disorder which presents with a classical pattern of mucocutaneous/soft tissue bleed, with pallor epistaxis and gum bleed being the most common presenting complaints.